A transformer‐less DC–DC converter with high voltage conversion ratio adopting inverting voltage lift cell - Ebrahim Babaei; Hamed Mashinchi Maheri; Mehran Sabahi (IET Circuits, Devices and Systems)
Abstract In this work, a high voltage gain dc‐dc converter is proposed based on a switched inductor cell. The proposed converter utilises an inverting switched capacitor cell at the output side to achieve high voltage gain. Extendibility of the proposed structure without applying the fundamental change to the topology is the merit of the proposed structure as well as the low voltage stress on the switches. The operation of the switches with the same duty cycle is the other advantage of the proposed converter. The steady‐state analysis of the proposed converter is discussed in detail. The proposed converter is investigated under real conditions in order to compare it with its operation under ideal conditions. The proposed structure is compared with other topologies presented in the literature, previously. Finally, the experimental results are given to prove the validity of the theoretical analysis.